Assessment of forest fires impacts on geoheritage: A study in the Estrela UNESCO Global Geopark, Portugal - Jéssica Gonçalves; Emanuel de Castro; Fábio Loureiro; Paulo Pereira (International Journal of Geoheritage and Parks)
The main purpose of this study was the development of a methodology to assess the potential impacts of forest fires on geoheritage through a systematic and practical approach. The proposed methodology was applied to the geoheritage of the Estrela UNESCO Global Geopark (UGGp) in Portugal, following a forest fire in August 2022 that affected approximately 15% of its geosites (22 out of 147). A total of 20 geosites were selected for analysis, including eight directly impacted by the fire and 12 that remained unaffected. The assessment framework integrates vulnerability and hazard factors. Vulnerability was quantified based on two primary criteria: geosites value and their educational and touristic uses. Each criterion was operationalized through defined parameters and indicators, supported by standardized guidelines for evaluation. Forest fire hazard data were obtained from the Portuguese Institute for the Conservation of Nature and Forests (ICNF). The degradation risk was calculated as a function of these two factors. The results indicate that the highest vulnerability level identified was “low,” signifying the absence of substantial loss in scientific value. However, discernible impacts on cultural, scenic and ecological values, and on educational/touristic uses were observed across most geosites. The maximum degradation risk was classified as “medium,” suggesting that the predominant granite and glacial landforms within the study area exhibit a relatively high degree of resilience to forest fire-induced damage. The findings underscore the importance of implementing targeted management strategies to mitigate the impacts of forest fires within the Estrela UGGp. Moreover, the methodology offers a transferable framework for geoheritage degradation risk assessment, which could be applied in diverse contexts to further enhance the understanding and conservation of geoheritage.